PCB machines optimitisation using multilevel genetic algorithm - Tan, Hock Chang. (2008)
This dissertation deals with optimization problems arising from automated printed circuit board (PCB) assembly. The organization of the production involves problems, starting form top-level tactical decisions at scheduling, through grouping and line balancing, to single machine optimization problems. This dissertation focuses on single machine optimization problems using Genetic Algorithms.